1988
DOI: 10.1677/joe.0.1160191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parasitism on plasma concentrations of growth hormone, somatomedin-C and somatomedin-binding proteins in calves

Abstract: A parasitic disease model (sarcocystosis) was used to study the effects of infection and associated plane of nutrition on GH and somatomedin-C (SM-C) patterns in plasma, and SM-C binding protein patterns in plasma from 4-month-old male Holstein calves. Calves, matched by age and rate of growth before the experiment, were divided into three treatment groups (n = 7). In the first (control), animals were uninfected and food was available ad libitum; in the second, animals were infected with Sarcocystis cruzi and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Increases in IGFBP-1 and -2 seem to restrict IGF-I activities, while a decrease in IGFBP-3 suggests an attempt to maximize the availability of remaining IGFs to the tissues. Elsasser et al [31] demonstrated reduced binding of IGF-I in calves due to restriction of intake and parasitism.…”
Section: Effect Of Nutritional Status On Circulat-ing Concentrations mentioning
confidence: 99%
“…Increases in IGFBP-1 and -2 seem to restrict IGF-I activities, while a decrease in IGFBP-3 suggests an attempt to maximize the availability of remaining IGFs to the tissues. Elsasser et al [31] demonstrated reduced binding of IGF-I in calves due to restriction of intake and parasitism.…”
Section: Effect Of Nutritional Status On Circulat-ing Concentrations mentioning
confidence: 99%
“…Furthermore, it was demonstrated in our previous study that the observed muscle effects exceeded any of the effects associated with the temporary slump in voluntary feed intake where direct nutritional effects of nutritional plane were addressed statistically through the use of the applied pair-feeding strategy. 7 Protein tyrosine nitration is a posttranslational chemical modification wherein the 3'-position of the affected tyrosine phenolic structure becomes nitrated. 42 Though thought of principally as a biomarker for oxynitrogen stress and disease, 43 we now know that nitration in low, well controlled biological circumstances such as the selective nitration of JAK2 kinase by growth hormone 27 functions as a process important to signal transduction events, possible countering hormone and cytokine pathway processes activated by phosphorylation while the high levels of production indicate pathology.…”
Section: Articlementioning
confidence: 99%
“…4 Growth deficits and associated cachectic and atrophic metabolic responses (anorexia, fever production, protein and fat mobilization, liver acute phase protein synthesis) to infection in the young are evident not only in changes in body weight gain or height velocity over time but also observable as changes in body composition. 5 Using models of parasitemediated progressive inflammatory disease in calves, [6][7][8] we characterized organ and tissue depot-specific changes in chemical body composition associated with reduced rate of weight gain and/or weight loss during parasitic infection. In particular, we observed that the pattern of change in fat and protein content of impacted tissues was not uniform as regards the extent to which different tissue depots were affected.…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, retained nitrogen (Elsasser et al, 1988) and body weight (BW) gain (Breier et al, 1988) have been correlated with circulating IGF-1 during feed restriction. Ogawa et al (1996) observed a negative correlation between net protein catabolism and plasma IGF-1 levels during GH treatment of fasting lambs.…”
Section: Introductionmentioning
confidence: 99%